Whole-mount RNA in situ hybridization of zebrafish embryos - Ünal, İsmail; Cansız, Derya; Beler, Merih; Alturfan, Ahmet Ata; Emekli Alturfan, Ebru (Humana Press Inc., 2024)
A commonly employed technique in molecular biology to evaluate the temporal and spatial expression of a certain gene is in situ hybridization. This method is an effective strategy to construct synexpression groups, co-expressed genes acting in shared biological processes, and to find new members of genes engaged in the same signaling pathways to discover similar spatial and temporal expression patterns in zebrafish embryos. The major disadvantage of this method is that RNA probes can penetrate within 2 days of post-fertilization embryos, and therefore, in later developmental stages, the probe can only reach the surface tissues. Further application of the method in histological sections will be required for a complete and accurate gene expression investigation. However, this method is highly effective at late embryogenesis and early larval stages for observing gene expression in endodermal derivatives and sensory organs. RNA probes for in situ hybridization can be prepared through in vitro transcription from plasmids carrying specific promoter elements and mRNA-specific cDNA, or an alternative polymerase chain reaction (PCR) method can be used through PCR amplification. This chapter describes the procedures for detecting gene expression in zebrafish embryos using whole-mount RNA in situ hybridization.
Keywords: In Situ Hybridization; Polymerase Chain Reaction; RNA Probe; Zebrafish Embryo